Two-dimensional flaky porphyrin metal organic framework / hydroxyethyl cellulose-based composite packaging film with photodynamic sterilization function as well as preparation method and application of two-dimensional flaky porphyrin metal organic framework / hydroxyethyl cellulose-based composite packaging film

By combining two-dimensional sheet Zn-TCPP with hydroxyethyl cellulose, a food packaging film with strong light dynamic antibacterial and ultraviolet shielding ability was prepared, which solved the poor antibacteriality and ultraviolet shielding of hydroxyethyl cellulose in the food packaging field. The problem of insufficient ability has achieved the extension of food shelf life and the improvement of biosafety.

CN119286066AActive Publication Date: 2025-01-10HUAQIAO UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411403944.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-01-10
Estimated Expiration
2044-10-09

AI Technical Summary

Technical Problem

Hydroxyethyl cellulose, as a food packaging film material, lacks antibacterial function and ultraviolet shielding ability, making it difficult to effectively extend the shelf life of food.

Method used

A two-dimensional sheet Zn-TCPP (zinc-based porphyrin metal organic framework) is combined with hydroxyethyl cellulose, and a composite film is prepared by ultrasonic synthesis and casting method to enhance the photodynamic antibacterial performance and ultraviolet shielding effect.

Benefits of technology

It significantly improves the antibacterial properties and UV shielding capabilities of food packaging film, extends the shelf life of food, and maintains biosafety and high transparency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119286066A_ABST
    Figure CN119286066A_ABST
Patent Text Reader

Abstract

The invention discloses a two-dimensional flaky porphyrin metal organic framework / hydroxyethyl cellulose-based composite packaging film with a photodynamic sterilization function as well as a preparation method and application of the two-dimensional flaky porphyrin metal organic framework / hydroxyethyl cellulose-based composite packaging film. The invention relates to a two-dimensional flaky porphyrin metal organic framework / hydroxyethyl cellulose based composite packaging film with photodynamic sterilization, which is prepared by reacting two-dimensional flaky Zn-TCPP and hydroxyethyl cellulose under the action of a cross-linking agent, the two-dimensional flaky Zn-TCPP is prepared by the following steps: carrying out a reaction on Zn (NO3) 2.6 H2O and racemic-tetra (4-hydroxyphenyl porphin) in N-N-diethyl formamide, and then carrying out ultrasonication, thereby obtaining the two-dimensional flaky Zn-TCPP. The two-dimensional flaky porphyrin metal organic framework modified hydroxyethyl cellulose with extremely high stability is adopted, the water solubility of the hydroxyethyl cellulose is effectively improved, the antibacterial effect is remarkably enhanced, and the prepared packaging film is high in antibacterial property, high in biological safety and good in mechanical property, has the dual effects of shielding ultraviolet rays and highly transmitting visible light, and has a good application prospect. The shelf life of food can be obviously prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a two-dimensional sheet-like porphyrin metal organic framework / hydroxyethyl cellulose-based composite packaging film with photodynamic sterilization function, a preparation method and application thereof, and belongs to the technical field of food packaging. Background Art

[0002] The development of high value-added chemicals and materials by replacing petrochemical raw materials with biomass raw materials is moving towards directional transformation, functionalization, intelligence, environmental friendliness, standardization, and comprehensive utilization. Hydroxyethyl cellulose (HEC) is one of the cellulose derivatives. Its molecules are rich in hydroxyl groups. Through chemical modification, it is easy to react with metal ions. Hydroxyethyl cellulose film is a new type of biomaterial with excellent biocompatibility, biodegradability and bioabsorbability. It can be gradually absorbed by the human body without causing harm to the human body. It can be used in food, medical, cosmetics and other fields. Hydroxyethyl cellulose is used in food packaging to effectively protect the quality and nutritional content of food. However, the disadvantage of pure hydroxyethyl cellulose as a food packaging film material is that it lacks antibacterial function and has poor UV shielding ability. Photodynamic sterilization, as a safe and effective antibacterial method, is an emerging means of food safety.

[0003] Photodynamic sterilization combines light of a specific wavelength, oxygen, and photosensitizers to generate reactive oxygen species (ROS), especially singlet oxygen ( 1 O2) can oxidize lipids, proteins and nucleic acids in microorganisms, leading to the death of microorganisms. Traditional thermal and chemical methods used for microbial control in the food industry can have adverse effects on food quality and bacterial resistance. Photodynamic sterilization, as a new innovative sterilization technology, has attracted widespread attention due to its good sterilization effect, environmental protection and safety.

[0004] Traditional photosensitizer porphyrin is a macromolecular planar heterocyclic compound formed by four pyrrole rings connected to each other by methylene bridges (=CH-). The atom at the center of porphyrin can coordinate with metal ions to form metal porphyrin. Porphyrin has the characteristics of strong biocompatibility, few side effects and can be effectively cleared by organisms. However, most porphyrins and their derivatives have the disadvantages of unstable properties and easy self-quenching under aqueous solution conditions, which limits their application.

[0005] In order to solve the problem that degradable hydroxyethyl cellulose has poor antibacterial properties and is rarely used in the field of food packaging, the inventors proposed a food composite packaging film with excellent photodynamic antibacterial properties, UV shielding properties and biosafety. Summary of the invention

[0006] The invention provides a two-dimensional flaky porphyrin metal organic framework / hydroxyethyl cellulose-based composite packaging film with photodynamic sterilization, a preparation method and application thereof. The invention uses Zn(NO3)2.6H2O, racemic-tetrakis(4-hydroxyphenylporphine) and NN-diethylformamide (DEF) as raw materials to prepare a zinc-based porphyrin metal organic framework, synthesizes the two-dimensional flaky metal porphyrin organic framework by ultrasound, and greatly improves the photodynamic antibacterial performance. Then, the two-dimensional flaky porphyrin metal organic framework is added to hydroxyethyl cellulose to prepare a film liquid, and a casting method is used to prepare the composite packaging film, so as to solve the problem that biomass hydroxyethyl cellulose is rarely used in the field of food packaging, enhance the antibacterial effect and ultraviolet shielding, and extend the shelf life of packaged food.

[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:

[0008] A two-dimensional lamellar porphyrin metal organic framework / hydroxyethyl cellulose-based composite packaging film with photodynamic sterilization, which is prepared by reacting two-dimensional lamellar Zn-TCPP (two-dimensional lamellar porphyrin metal organic framework) and hydroxyethyl cellulose under the action of a crosslinking agent;

[0009] The two-dimensional sheet Zn-TCPP was prepared by reacting Zn(NO3)2.6H2O and racemic-tetrakis(4-hydroxyphenylporphine) in NN-diethylformamide (DEF) and then ultrasonically crushing it.

[0010] The present application prepares a composite membrane from a two-dimensional sheet-like porphyrin metal organic framework Zn-TCPP and HEC, which can effectively solve the problem of poor antibacterial performance of HEC, has high biological safety, has the dual effects of shielding ultraviolet rays and high visible light transmittance, and can significantly extend the shelf life of food.

[0011] In porphyrin MOFs, porphyrin or metalloporphyrin as an organic ligand is combined with metal ions or ion clusters through coordination bonds to become the building blocks in the MOFs structure. The porphyrin units are arranged periodically in the MOFs structure, and the monodispersed state effectively prevents the self-aggregation and self-quenching of porphyrin, thereby improving the physical and chemical properties of porphyrin. At the same time, the porphyrin loading capacity of MOFs is high, and the porous structure is conducive to the diffusion of singlet oxygen, thus improving the photodynamic properties of the material.

[0012] Compared with two-dimensional layered Zn-TCPP, two-dimensional sheet Zn-TCPP has a larger effective specific surface area, more complete contact with oxygen, stronger singlet oxygen produced, and stronger photodynamic bactericidal performance. When added to hydroxyethyl cellulose, the antibacterial properties of the hydroxyethyl cellulose film are enhanced, the adhesion and accumulation of bacteria are reduced, and the film can better exert its antibacterial effect, and no high temperature and harmful substances will be generated during the photodynamic sterilization process.

[0013] In order to improve the reaction efficiency and product purity, the preparation method of two-dimensional sheet Zn-TCPP includes the following steps:

[0014] 1) Zn-TCPP was synthesized by a one-pot solvothermal method: Zn(NO3)2.6H2O and meso-tetrakis(4-hydroxyphenylporphine) were dissolved in a mixed solvent of NN-diethylformamide (DEF) and H2O, placed in a glass bottle sealed with a polytetrafluoroethylene cap, reacted at 80-85°C for 24-48h, washed with NN-diethylformamide (DEF) and centrifuged, and the resulting precipitate was dried to obtain a two-dimensional layered purple crystalline Zn-TCPP;

[0015] 2) The two-dimensional layered Zn-TCPP is ultrasonically crushed in water and freeze-dried to obtain the two-dimensional flaky Zn-TCPP.

[0016] The two-dimensional sheet-like porphyrin metal organic framework prepared above generates strong active oxygen and is used for preparing hydroxyethyl cellulose composite membrane.

[0017] To further ensure the antibacterial effect, in step 1), the molar ratio of Zn(NO3)2.6H2O and meso-tetrakis(4-hydroxyphenylporphine) is 1:(0.1-0.3); in the mixed solvent, the volume ratio of NN-diethylformamide (DEF) and H2O is 3:(0.8-1.2); and drying is performed at 50-60°C for 5-12 hours.

[0018] In order to improve the photodynamic antibacterial performance, step 2) is: disperse the two-dimensional layered Zn-TCPP in ultrapure water by ice bath ultrasonication, freeze-dry, and obtain a two-dimensional porphyrin metal organic framework Zn-TCPP; the ice bath ultrasonication time is 0.5 to 1 h, and the ultrasonic power is 300 to 600 w; further preferably, the ice bath ultrasonication time is 1 h, and the ultrasonic power is 600 w.

[0019] By comparing the two-dimensional layered Zn-TCPP before dispersion and the two-dimensional flake Zn-TCPP obtained by dispersion at different ultrasonic powers and ultrasonic times, it is found that the two-dimensional flake Zn-TCPP of the present invention has good stability in water. The two-dimensional flake Zn-TCPP obtained by 600W ultrasound for 60 minutes has the most stable optical properties and is more capable of generating singlet oxygen under the irradiation of white light LED lamps.

[0020] The present application uses the indicator 9,10-anthracenediyl-bis(methylene)-dimalonic acid (ABDA) to detect the strength of singlet oxygen generated by two-dimensional layered Zn-TCPP.

[0021] The preparation method of the above-mentioned two-dimensional porphyrin metal organic framework / hydroxyethyl cellulose-based composite packaging film with photodynamic sterilization is: disperse the two-dimensional flaky Zn-TCPP (600W, 60min) in deionized water, add hydroxyethyl cellulose and stir continuously, and after the solution is stirred from turbid to clear, add the crosslinking agent citric acid monohydrate and the plasticizer glycerol and stir, lay the film by casting method, and dry in a vacuum drying oven to obtain a composite film.

[0022] The above-mentioned two-dimensional lamellar porphyrin metal organic framework / hydroxyethyl cellulose-based composite material with photodynamic sterilization has two-dimensional lamellar porphyrin metal organic framework Zn-TCPP and HEC as main raw materials, citric acid monohydrate as cross-linking agent, and glycerol as plasticizer to prepare film-forming liquid, and then prepared into film by casting method, and has excellent ultraviolet shielding, antibacterial activity and biocompatibility.

[0023] The dosage of the above hydroxyethyl cellulose is 3-5 g / 100 ml water, that is, 3-5 g hydroxyethyl cellulose is added to every 100 ml water.

[0024] In order to improve the antibacterial and mechanical properties of the obtained membrane, the mass dosage of the two-dimensional sheet Zn-TCPP is 0.3% to 3% of the mass of hydroxyethyl cellulose HEC; the mass dosage of citric acid monohydrate is 20 to 25% of the mass of hydroxyethyl cellulose HEC; and the mass dosage of glycerol is 10 to 15% of the mass of hydroxyethyl cellulose HEC.

[0025] In order to ensure the antibacterial properties of the obtained composite film, as one of the specific implementation schemes, the two-dimensional flaky Zn-TCPP (600W, 60min) is ultrasonically dispersed in ultrapure water, hydroxyethyl cellulose is added and stirred at 400-600rpm for 1-3h, monohydrate citric acid and glycerol are added, stirred at 400-600rpm for 2-4h, and the film is laid by a casting method and dried in a vacuum drying oven at a temperature of 40-60°C for 5-12h to obtain a two-dimensional flaky porphyrin metal organic framework / hydroxyethyl cellulose-based composite packaging film with photodynamic sterilization.

[0026] The above-mentioned two-dimensional sheet-like porphyrin metal organic framework / hydroxyethyl cellulose-based composite packaging film with photodynamic sterilization function is used for food packaging and food preservation, and can also be directly used for shielding ultraviolet rays and / or for antibacterial purposes.

[0027] The hydroxyethyl cellulose-based porphyrin metal organic framework composite membrane does not require a complicated reaction process and the preparation method is very simple.

[0028] The inventors have found through research that the two-dimensional sheet-like porphyrin metal organic framework Zn-TCPP obtained by ultrasonically crushing the two-dimensional layered porphyrin metal organic framework Zn-TCPP has a stronger ability to generate active oxygen, a larger effective specific surface area, more sufficient contact with oxygen, stronger singlet oxygen generated, and stronger photodynamic sterilization performance, thereby enhancing the antibacterial performance of the hydroxyethyl cellulose film, so that the film can better exert its antibacterial effect, and will not generate high temperature and harmful substances during the photodynamic sterilization process, and it meets the development requirements of green chemistry; the two-dimensional sheet-like Zn-TCPP can generate active oxygen (ROS) under light, such as singlet oxygen ( 1 O2) or hydroxyl radicals (·OH), which can oxidize lipids, proteins and nucleic acids in microorganisms, leading to the death of microorganisms. The prepared composite film has a simple synthesis method and has excellent photodynamic antibacterial activity, UV shielding performance and biocompatibility. With the increase of the content of two-dimensional sheet Zn-TCPP, the antibacterial performance and UV shielding ability of the composite film under light are enhanced.

[0029] The temperature not specifically specified in the present application is all completed at room temperature, which includes a temperature range of 20 to 40° C. The drying conditions not specifically specified are dried to constant weight.

[0030] The technologies not mentioned in the present invention are all referred to the prior art.

[0031] The present invention achieves the following beneficial effects:

[0032] 1) The two-dimensional sheet-like Zn-TCPP of the present invention has a stronger ability to generate active oxygen than the two-dimensional layered Zn-TCPP, and the photodynamic antibacterial activity is significantly improved. The raw material porphyrin has excellent biocompatibility and photophysical properties;

[0033] 2) The two-dimensional sheet Zn-TCPP of the present invention has good stability in water;

[0034] 2) The hydroxyethyl cellulose composite film prepared based on the two-dimensional sheet Zn-TCPP of the present invention is simple to prepare, with bio-based HEC as the substrate, a wide range of raw materials, low cost, high biocompatibility, and the prepared composite film has high photodynamic antibacterial activity;

[0035] 3) The present invention changes the water solubility of hydroxyethyl cellulose, solves the application problem of hydroxyethyl cellulose in food packaging, and expands the application direction;

[0036] 4) The food packaging film prepared by the present invention has high transparency, not only has extremely high transmittance in the visible light region, but also has obvious shielding effect against ultraviolet rays, which is beneficial to the preservation of the food inside;

[0037] 5) The food packaging film prepared by the present invention has excellent mechanical properties and can well meet the food packaging requirements;

[0038] 6) The photodynamic sterilization used is a new innovative sterilization technology with good sterilization effect, environmental protection and safety. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 The SEM (ab) of the two-dimensional layered Zn-TCPP obtained in the present invention, the SEM (c) of the two-dimensional sheet-like Zn-TCPP, and the FT-IR spectra (d) of the two-dimensional layered Zn-TCPP and the two-dimensional sheet-like Zn-TCPP;

[0040] Figure 2 The UV absorption spectra of ABDA solutions of two-dimensional layered Zn-TCPP and two-dimensional sheet Zn-TCPP after irradiation for 30 minutes;

[0041] Figure 3 The SEM (a), FT-IR spectrum (b), XRD spectrum (c) and UV spectrum (d) of the thin films obtained in each example;

[0042] Figure 4 The tensile stress-strain spectrum of each film is shown in Figure 2.

[0043] Figure 5 The obtained antibacterial images of the films in each case;

[0044] Figure 6 The pictures showing the effects of the films used to preserve strawberries in each example are actual photos of the seven-day packaging. DETAILED DESCRIPTION

[0045] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.

[0046] In each case, unless otherwise specified, the temperature operation was completed at room temperature, which was 20 to 30°C.

[0047] Example 1

[0048] 0.1mmol Zn(NO3)2.6H2O and 0.02mmol meso-tetrakis(4-hydroxyphenylporphine) were dissolved in a mixed solvent of NN-diethylformamide (DEF) / H2O (V / V=3:1, 4ml), placed in a 20ml sealed polytetrafluoroethylene capped glass bottle, reacted at 85°C for 48h, washed with DEF and centrifuged, and the precipitate obtained by centrifugation was dried in a vacuum drying oven at 60°C overnight (12h) to obtain a two-dimensional layered Zn-TCPP as a two-dimensional layered purple crystal.

[0049] The two-dimensional layered Zn-TCPP was ultrasonically dispersed in deionized water in an ice bath, and then freeze-dried to obtain a two-dimensional sheet Zn-TCPP. The following two-dimensional sheet samples were obtained by using different ultrasonic powers and ultrasonic times: Zn-TCPP (300W, 30min), Zn-TCPP (300W, 60min), Zn-TCPP (600W, 30min), and Zn-TCPP (600W, 60min).

[0050] Figure 1 In the figure, (a) is the SEM image of the two-dimensional layered Zn-TCPP, (b) is the energy dispersive X-ray spectroscopy (EDS) element mapping (Zn, C, N, O), and (c) is the SEM image of the two-dimensional sheet Zn-TCPP. The scanning electron microscope (SEM) image of Zn-TCPP clearly shows that Zn-TCPP has a large lateral size and an ordered stacked layer structure ( Figure 1 (a)), and these layers are tightly packed on a very clean surface. Energy dispersive spectroscopy (EDS) elemental mapping shows that Zn, C, N, and O elements are uniformly distributed in 2DZn-TCPP ( Figure 1 In (b), the two-dimensional layered Zn-TCPP was broken by ultrasonic treatment with different powers and times. Figure 1 The SEM image in (c) clearly shows that the layered structure of Zn-TCPP is ultrasonically dispersed into flakes and reduced in size. The two-dimensional layered Zn-TCPP is more uniformly dispersed into flakes when ultrasonically dispersed at 600 W for 60 min.

[0051] Infrared test of Zn-TCPP before and after ultrasonic dispersion: the sample was mixed with dry KBr powder and analyzed by FTIR spectrometer in the range of 400-4000cm-1, 32 scans, and a resolution of 4cm-1. The analysis is as follows:

[0052] Figure 1 (d) shows the FT-IR spectra of two-dimensional layered Zn-TCPP and two-dimensional sheet Zn-TCPP formed by different ultrasonic times and powers. Figure 1 As shown in (d), the FT-IR spectrum of TCPP is at 1694 cm -1 There is an obvious absorption peak at 3319 cm -1 The absorption peaks at 100° belong to the stretching vibration of the NH bond. These peaks disappear in Zn-TCPP, indicating that TCPP and Zn 2+ The coordination reaction occurred. Several infrared characteristic absorption peaks of Zn-TCPP are 3425cm -1 (-OH), 1625cm -1 (-COO -) and 1403cm -1 (-C=N-). The two-dimensional layered Zn-TCPP was broken by ultrasonic treatment with different powers and times. From the infrared spectrum, it can be seen that the structure of the two-dimensional sheet Zn-TCPP obtained by ultrasonic treatment has basically not changed, indicating that the two-dimensional layered Zn-TCPP and the two-dimensional sheet Zn-TCPP have good stability in water. Figure 1 Among them, Zn-TCPP (300W, 30min), Zn-TCPP (300W, 60min), Zn-TCPP (600W, 30min) and Zn-TCPP (600W, 60min) are two-dimensional flake Zn-TCPP obtained by ultrasonic dispersion under different ultrasonic powers and ultrasonic times. Figure 1 The Zn-TCPP at the bottom is the two-dimensional layered Zn-TCPP before ultrasonic dispersion.

[0053] UV spectrum test: The two-dimensional layered Zn-TCPP and two-dimensional t-Zn-TCPP dispersions were irradiated under a white light LED lamp (100W) for different time periods, and their absorption spectra were scanned. It was found that the absorbance of the two-dimensional flake Zn-TCPP (600W, 60min) was reduced to 63.88% of the initial absorbance, which was better than the optical properties of the two-dimensional layered Zn-TCPP. The optical properties of the two-dimensional flake Zn-TCPP obtained at 600W ultrasound for 60min were the most stable, and the absorbance remained basically unchanged after 40min of illumination. Zn-TCPP (600W, 60min) was selected for subsequent photodynamic experiments.

[0054] Singlet oxygen test analysis: Weigh 10.3 mg of ABDA powder (9,10-anthracenediylbis(methylene)-dimalonic acid), dissolve it in DMSO (dimethyl sulfoxide) and dilute to 5 mL, the concentration is 5.0×10 -3 mol / L mother solution, store in the dark. Using ultrapure water as solvent, prepare mother solutions of Zn-TCPP (two-dimensional layered Zn-TCPP) and t-Zn-TCPP (two-dimensional sheet Zn-TCPP) with a concentration of 1 mg / mL. Take 15μL ABDA mother solution and mix it with 30μL Zn-TCPP and t-Zn-TCPP mother solutions, add ultrapure water, and prepare the total volume of the final solution to 1.5mL. The final concentration of porphyrin MOF in this mixed solution is 0.02mg / mL. Take 15μL of ABDA mother solution and mix it with ultrapure water to make the final solution volume 1.5mL, which is used as the blank group. The final concentration of ABDA in all groups is 5.0×10 -5 mol / L. Figure 2(a) shows the relative absorbance changes at 423 nm of two-dimensional layered Zn-TCPP and two-dimensional sheet Zn-TCPP formed by ultrasound with different ultrasonic time and power. Figure 2 (b) shows the UV absorption spectra of ABDA solution of two-dimensional layered Zn-TCPP and two-dimensional sheet Zn-TCPP formed by different ultrasonic time and power after irradiation for 30 minutes. Figure 2 The UV absorption spectrum of Zn-TCPP (600W, 60min) shows that after 30min of illumination, the ABDA solution 1 The intensity of the characteristic absorption peak corresponding to the O2-specific indicator 9,10-anthracenediylbis(methylene)-dimalonic acid (ABDA) is significantly reduced. ABDA is an anthracene derivative that can be oxidized by singlet oxygen to form peroxides, resulting in a decrease in the absorbance of ABDA. According to the attenuation trend of ABDA, Zn-TCPP (600W, 60min) has a stronger ability to produce singlet oxygen under white light LED light.

[0055] Example 2

[0056] Preparation of hydroxyethyl cellulose composite membrane:

[0057] Add 4 g of hydroxyethyl cellulose to 100 ml of ultrapure water and stir at 500 rpm for 1 h. When the solution is clear, add 1 g of citric acid monohydrate crosslinker and 0.6 g of plasticizer glycerol and stir for 2 h at a stirring rate of 600 rpm. Pour 15 mL of the membrane liquid on a 100 mm × 100 mm square plastic culture dish and dry it in a vacuum drying oven at 50 ° C overnight (12 h) to obtain a pure HEC film.

[0058] Example 3

[0059] 12 mg of two-dimensional flaky Zn-TCPP (600 W, 60 min) was ultrasonically dispersed in 100 ml of ultrapure water, 4 g of hydroxyethyl cellulose was added and stirred at 500 rpm for 1 h, the solution changed from turbid to clear, then 1 g of citric acid monohydrate crosslinker and 0.6 g of plasticizer glycerol were added and stirred for 2 h at a stirring rate of 600 rpm. 15 ml of the membrane liquid was poured on a 100 mm × 100 mm square plastic culture dish and dried in a vacuum drying oven at 50 ° C overnight (12 h).

[0060] Example 4

[0061] 20 mg of two-dimensional flaky Zn-TCPP (600 W, 60 min) was ultrasonically dispersed in 100 ml of ultrapure water, 4 g of hydroxyethyl cellulose was added and stirred at 500 rpm for 1 h, the solution changed from turbid to clear, then 1 g of monohydrate citric acid crosslinker and 0.6 g of plasticizer glycerol were added and stirred for 2 h at a stirring rate of 600 rpm. 15 ml of the membrane liquid was poured on a 100 mm × 100 mm square plastic culture dish and dried in a vacuum drying oven at 50 ° C overnight (12 h).

[0062] Example 5

[0063] 40 mg of two-dimensional flaky Zn-TCPP (600 W, 60 min) was ultrasonically dispersed in 100 ml of ultrapure water, 4 g of hydroxyethyl cellulose was added and stirred at 500 rpm for 1 h, the solution changed from turbid to clear, then 1 g of monohydrate citric acid crosslinker and 0.6 g of plasticizer glycerol were added and stirred for 2 h at a stirring rate of 600 rpm. 15 ml of the membrane liquid was poured on a 100 mm × 100 mm square plastic culture dish and dried in a vacuum drying oven at 50 ° C overnight (12 h).

[0064] Example 6

[0065] 120 mg of two-dimensional flaky Zn-TCPP (600 W, 60 min) was ultrasonically dispersed in 100 ml of ultrapure water, 4 g of hydroxyethyl cellulose was added and stirred at 500 rpm for 1 h, the solution changed from turbid to clear, then 1 g of monohydrate citric acid crosslinker and 0.6 g of plasticizer glycerol were added and stirred for 2 h at a stirring rate of 600 rpm. 15 ml of the membrane liquid was poured on a 100 mm × 100 mm square plastic culture dish and dried in a vacuum drying oven at 50 ° C overnight (12 h).

[0066] The performance of the membranes obtained in the above embodiments was tested.

[0067] Morphology test of the film: The surface morphology of different composite films was observed by SEM. As can be seen from Figure 3(a), the surface of the HEC film is relatively flat, without obvious cracks and wrinkles. After adding Zn-TCPP (600W, 60min), the surface of the film showed typical flaky particles. With the increase of the doping content of Zn-TCPP (600W, 60min), its distribution density in the film surface gradually increased, and the film surface became rough, indicating that it was successfully incorporated into the HEC matrix as a filler and was closely combined with the film components.

[0068] Infrared testing of the film: The film sample was measured using an attenuated total reflectance (ATR) accessory, with 16 scans in the wavelength range of 4000-400cm -1 , resolution 4cm -1 , the analysis is as follows: Figure 3As shown in (b), the interaction between HEC group and Zn-TCPP (600W, 60min) caused a slight change in the functional group peak and intensity of the film. -1 The characteristic peak is -OH, 2922cm -1 The characteristic peak at 1720 cm -1 The characteristic peak at 1033 cm is C=O. -1 The characteristic peak at is CO. With the increase of Zn-TCPP (600W, 60min) content, the peak of HEC / Zn-TCPP (600W, 60min) film shifts to a lower wavenumber, indicating that hydrogen bonds are formed between the carboxyl groups in Zn-TCPP (600W, 60min) and the oxygen-containing groups (such as hydroxyl and carboxyl) in the HEC matrix.

[0069] The XRD diffraction spectrum of the film is shown in ( Figure 3 In (c), the peak at 21.25° indicates that HEC (hydroxyethyl cellulose) is an amorphous non-crystalline mixture. In addition, the main diffraction peak appeared at 17.61°, and gradually increased with the increase of Zn-TCPP (600W, 60min), proving that the two-dimensional porphyrin sheet Zn-TCPP (600W, 60min) was successfully incorporated into the hydroxyethyl cellulose membrane, and its structure was not damaged after being embedded in the biological matrix, and it can still retain a relatively complete structure, indicating that Zn-TCPP (600W, 60min) has good compatibility in hydroxyethyl cellulose.

[0070] Film transparency test: (UV-Visible) (PerkinELmer) ultraviolet-visible spectrophotometry (UV / vis) was used to record the ultraviolet transmittance of film samples in the range of 200 to 800 nm. For food packaging, high transparency can facilitate the observation of the state of the contents, and common commercially available cling films have very high ultraviolet transmittance. The porphyrin metal organic framework / hydroxyethyl cellulose packaging film prepared in this application also has high transparency. With the increase of the doping content of Zn-TCPP (600W, 60min), the appearance color of the film gradually deepens from colorless to reddish brown. Ultraviolet blocking ability and transparency are of great significance in food packaging. Ultraviolet blocking ability helps protect food from damage by ultraviolet rays, and a certain degree of transparency enables us to identify the specific condition of food. After adding two-dimensional flake Zn-TCPP (600W, 60min), the ultraviolet transmittance of the film at 600nm, 560nm, and 430nm is significantly reduced. Figure 3As shown in (d), with the increase of Zn-TCPP (600W, 60min) content, the UV transmittance at 405nm-450nm decreases to 0, and the wave number range of UV shielding expands, indicating that the composite film has a strong ability to shield UV, which can reduce the loss and deterioration of food nutrients caused by UV radiation during transportation or storage. Overall, the transmittance of the film in the visible light region can also have a certain UV shielding effect, which is beneficial to the preservation of the food inside.

[0071] Mechanical properties test of the film: Compared with the pure HEC film, after adding Zn-TCPP (600W, 60min), the internal hydrogen bond crosslinking degree is improved, and the elongation at break of the composite film is significantly increased, indicating that the composite material improves the ductility of the film ( Figure 4 ). When the doping amount of Zn-TCPP (600W, 60min) is 0.3%, the tensile strength of the film decreases, and the two-dimensional sheet-like metal organic framework partially agglomerates, resulting in a decrease in the mechanical properties of the material. When the added porphyrin MOF reaches a certain level, the mechanical properties of the material are no longer improved. Due to the weak interfacial adhesion, the tensile strength of the composite material is reduced.

[0072] Film antibacterial performance test: The plate count method in GB / T 37206-2018 standard was used to determine the antibacterial activity of the film against Staphylococcus aureus and Escherichia coli. Staphylococcus aureus and Escherichia coli suspensions were cultured in advance and then diluted to 10 7 CFU / mL. During the test, different films of equal mass (5 mg) were added to the EP tube, a certain bacterial suspension (20 μL) was dropped onto different films, and then illuminated with LED white light for 0 min, 5 min, 10 min, 15 min, 20 min, 30 min, incubated at 37 ° C for 1 h, diluted with phosphate buffer solution (PBS; pH = 7.4), and then 100 μL of the diluted bacterial suspension was applied to the LB plate, incubated at 37 ° C for 24 h, and the antibacterial properties of the film were evaluated by the colony counting method.

[0073] Figure 5 Escherichia coli (a) and Staphylococcus aureus (b) on each film under LED white light (light power density of 135 mW cm -2 ) Photos of bacterial colonies on the plate at 0min, 5min, 10min, 15min, 20min, and 30min under light. Figure 5As shown, the antibacterial phenomenon of the HEC film under dark conditions is not obvious. The film with the addition of Zn-TCPP (600W, 60min) can inhibit the growth of bacteria, and the bacterial survival rate decreases as the illumination increases. At the same time, within the same illumination time, as the content of Zn-TCPP (600W, 60min) increases, the inhibitory effect of the HEC / Zn-TCPP (600W, 60min) composite film becomes stronger and stronger. The antibacterial rates of the HEC / Zn-TCPP (600W, 60min) composite film of Example 6 against Staphylococcus aureus and Escherichia coli were 99.9% and 99.7%, respectively, when illuminated for 15 minutes.

[0074] Fresh strawberries were selected for packaging and preservation experiments. The prepared film was cut into 100mm×100mm sizes and wrapped with fresh strawberries. The films were stored at 25℃ and 50% RH for 7 days. The strawberries were photographed and recorded every day. On the 7th day, samples were taken from the surface of the strawberries to detect the number of surface colonies. Figure 6 As shown in the figure, the strawberries wrapped in pure HEC at room temperature have the highest degree of corruption. This is due to the airtightness of HEC. The strawberries cannot breathe and exchange gases with the outside world. The moisture accumulated on the inside of the plastic wrap is more likely to breed bacteria and mold. In contrast, only 80% of the control group exposed to the air showed signs of mold and blackening. As the content of Zn-TCPP (600W, 60min) increases, the degree of decay tends to decrease. Among them, the film effects of Examples 5 and 6 are excellent, with no mold or rot for 7 days. In summary, the above results show that the two-dimensional sheet-like porphyrin metal organic framework-based hydroxyethyl cellulose composite antibacterial film prepared in this study has excellent ultraviolet shielding, antibacterial activity and biocompatibility, and has a good effect of extending the shelf life of food.

Claims

1. A two-dimensional sheet-like porphyrin metal organic framework / hydroxyethyl cellulose-based composite packaging film with photodynamic sterilization, characterized in that: It is prepared by the reaction of two-dimensional sheet Zn-TCPP and hydroxyethyl cellulose under the action of a crosslinking agent; The two-dimensional sheet Zn-TCPP is prepared by reacting Zn(NO3)2.6H2O and racemic-tetrakis(4-hydroxyphenylporphine) in NN-diethylformamide and then ultrasonically crushing it.

2. The two-dimensional sheet-like porphyrin metal organic framework / hydroxyethyl cellulose-based composite packaging film with photodynamic sterilization as claimed in claim 1, characterized in that: The preparation method of two-dimensional sheet Zn-TCPP comprises the following steps: 1) Zn-TCPP was synthesized by a one-pot solvothermal method: Zn(NO3)2.6H2O and meso-tetrakis(4-hydroxyphenylporphine) were dissolved in a mixed solvent of NN-diethylformamide and H2O, reacted at 80-85°C for 24-48h, washed with NN-diethylformamide and centrifuged, and the obtained precipitate was dried to obtain a two-dimensional layered Zn-TCPP; 2) The two-dimensional layered Zn-TCPP is ultrasonically crushed in water and freeze-dried to obtain the two-dimensional flaky Zn-TCPP.

3. The two-dimensional sheet-like porphyrin metal organic framework / hydroxyethyl cellulose-based composite material with photodynamic sterilization as claimed in claim 2, characterized in that: In step 1), the molar ratio of Zn(NO3)2.6H2O and meso-tetrakis(4-hydroxyphenylporphine) is 1:(0.1-0.3); in the mixed solvent, the volume ratio of NN-diethylformamide and H2O is 3:(0.8-1.2); and drying is performed at 50-60°C for 5-12 hours.

4. The two-dimensional sheet-like porphyrin metal organic framework / hydroxyethyl cellulose-based composite packaging film with photodynamic sterilization as claimed in claim 2 or 3, characterized in that: Step 2) is: dispersing the two-dimensional layered Zn-TCPP in ultrapure water by ice bath ultrasonication, and freeze drying to obtain the two-dimensional flake Zn-TCPP; wherein the ice bath ultrasonic dispersion time is 0.5 to 1 hour, and the power is 300 to 600 W.

5. A method for preparing a two-dimensional sheet-like porphyrin metal organic framework / hydroxyethyl cellulose-based composite packaging film with photodynamic sterilization according to any one of claims 1 to 4, characterized in that: The two-dimensional sheet Zn-TCPP was ultrasonically dispersed in water, hydroxyethyl cellulose was added and stirred continuously, and after the solution was stirred from turbid to clear, a crosslinking agent citric acid monohydrate and a plasticizer glycerol were added and stirred, and a film was spread by a casting method and dried to obtain a composite membrane.

6. The preparation method according to claim 5, characterized in that: The dosage of hydroxyethyl cellulose is 3-5g / 100ml water.

7. The preparation method according to claim 5 or 6, characterized in that: The mass dosage of two-dimensional sheet Zn-TCPP is 0.3% to 3% of the mass of hydroxyethyl cellulose; the mass dosage of monohydrate citric acid is 20% to 25% of the mass of hydroxyethyl cellulose; and the mass dosage of glycerol is 10% to 15% of the mass of hydroxyethyl cellulose.

8. The preparation method according to claim 5 or 6, characterized in that: The two-dimensional flaky Zn-TCPP was ultrasonically dispersed in ultrapure water, hydroxyethyl cellulose was added and stirred at 400-600 rpm for 1-3 hours, then citric acid monohydrate and glycerol were added, stirred at 400-600 rpm for 2-4 hours, and the film was laid by a casting method and dried in a vacuum drying oven at a temperature of 40-60°C for 5-12 hours to obtain a two-dimensional flaky porphyrin metal organic framework / hydroxyethyl cellulose-based composite packaging film with photodynamic sterilization.

9. Use of the two-dimensional sheet-like porphyrin metal organic framework / hydroxyethyl cellulose-based composite packaging film with photodynamic sterilization according to any one of claims 1 to 4, characterized in that: Used for food packaging and food preservation.

10. Use of the two-dimensional sheet-like porphyrin metal organic framework / hydroxyethyl cellulose-based composite packaging film with photodynamic sterilization according to any one of claims 1 to 4, characterized in that: Used to block UV rays, and / or for antibacterial purposes.

Citation Information

Patent Citations

  • Preparation method of two-dimensional tetracarboxylphenylporphyrin metal organic framework film

    CN111118533A

  • Preparation method and application of photodynamic / photothermal synergistic antibacterial MOF-based packaging film

    CN116396512A

  • Zirconium-based metal-organic framework material as well as preparation method and application thereof

    CN118002200A

  • Ultra-small NANO metal organic framework material and preparation method thereof

    US20240209158A1